Role of SARS-CoV-2-specific memory B cells promoting immune protection after booster vaccination in solid organ transplantation - Donadeu, Laura; Gomez-Olles, Susana; Casanova, Franc; Torija, Alba; Lopez-Meseguer, Manuel; Boada-Pérez, Meritxell; Kervella, Delphine; Crespo, Elena; Carrera-Muñoz, Claudia; Campos-Varela, Isabel; Castells, Lluís; Cortese, Maria F.; et al. (Frontiers in Immunology, 2024)
Solid organ transplant (SOT) recipients display weak seroconversion and neutralizing antibodies (NAb) responses after SARS-CoV-2 vaccination and remain at risk of severe COVID-19. B-cell memory is the hallmark of serological immunity, but their role driving successful vaccine responses and immune protection in SOT is unclear.We investigated the function and interplay of SARS-CoV-2-specific memory B cells (mBc), different cytokine-producing T-cells and cross-reactive NAb, driving seroconversion and protection against COVID-19 in two cohorts. First, in a large cohort of 148 SOT and 32 immunocompetent individuals undergoing several vaccinations and afterwards, in 25 SOT participating in a randomized controlled trial in which we assessed two different immunosuppressive strategies to allow successful seroconversion and memory-cell responses after booster vaccination.We corroborate previous findings that B and T-cell memory responses are weaker and more delayed in SOT patients than immunocompetent (IC) individuals; however, within the SOT cohort, we find that these responses are relatively stronger and more robust in patients not receiving mycophenolate mofetil (MMF)-based therapies. Anti-Spike IgG titers strongly correlated with RBD-specific IgG-producing mBc, both displaying broad viral cross-reactivity. Pre-booster SARS-CoV-2-specific mBc and IL2producing T cells accurately predicted NAb seroconversion (AUC 0.828) and protection against severe COVID-19. While switching unresponsive SOT from CNI/MMF to low-exposure CNI/mTOR-i favored wider SARS-CoV-2-specific immune responses after a 4 th booster vaccination, preformed RBD-specific mBc predicted NAb seroconversion.Our study adds new insight on the pathobiology of immune memory and highlights the pivotal role of SARS-CoV-2-specific mBc promoting immune protection in SOT patients.